Espaços de turismo e de lazer urbanos: uma leitura geográfica - Rodrigues, Adyr Balastreri (2006)
This article recognizes the increasing importance of tourism due to the growth of urbanization by appreciating the value of the third sector as labor force. Facts and changes in social structures generate expectations and practices that multiply and diversify the urban spaces for leisure and tourism. The presence of thematic parks and shopping centers, standardized spaces for leisure, makes us think about the difference between space and place, world lived, and the concepts of territory and territoriality which consider the use of space as a means to appreciate the ideology of local development and tourism as a way to generate cultural codes based on images that replace reality and persuade people to follow patterns and behaviors imposed by consuming society. This article presents a definition of spaces for leisure and tourism by incorporating the geographic concepts of place, territory and space. It also questions the alienated consumption, leisure activities, the loss of open public spaces and spatial segregation of public and private equipment and the use of cultural heritage for the purpose of leisure and tourism.